Psychosocial burden and working conditions during the COVID-19 pandemic in Germany: The VOICE survey among 3678 health care workers in hospitals - Morawa, Eva; Schug, Caterina; Geiser, Franziska; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Weidner, Kerstin; Hiebel, Nina; Borho, Andrea; Erim, Yesim (Journal of psychosomatic research, 2021)
Objective: The aim of this cross-sectional web-based study was to examine self-reported mental distress, psychosocial burdens, working conditions and potential risk and protective factors for depressive and anxiety symptoms during the COVID-19 pandemic in health care workers (HCW). Methods: In the largest survey on mental health of HCW conducted during the first wave of COVID-19 in Europe (N = 8071 HCW), we investigated depressive (Patient Health Questionnaire-2, PHQ-2), and anxiety symptoms (Generalized Anxiety Disorder-2, GAD-2), working conditions, and psychosocial burden of 3678 HCW of three health care professions in hospitals: physicians (n = 1061), nurses (n = 1275), and medical technical assistants (MTA, n = 1342). Results: The prevalence of clinically significant levels of depressive and anxiety symptoms was 17.4% and 17.8% for physicians, 21.6% and 19.0% for nurses, and 23.0% and 20.1% for MTA, respectively. All three professions demonstrated significantly elevated PHQ-2 and GAD-2 scores, when compared with general German population before the pandemic, but lower scores in relation to that during the pandemic. Multiple linear regression analyses revealed that higher levels of depressive symptoms were associated with insufficient recovery during leisure time, increased alcohol consumption, and less trust in colleagues in difficult situations at work. In addition, elevated anxiety scores were related to increased fear of becoming infected with COVID-19. Conclusion: During the pandemic HCW demonstrated a lower burden of mental distress compared to the general population. Nevertheless, a high percentage of HCW demonstrates psychosocial distress, so that the establishment of regular mental health screening and prevention programmes for HCW is indicated.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Anxiety; COVID-19; Depression; Health care; Mental health; Working conditions